Simultaneous synthesis of H2, O2, and N2 via an innovatory energy system in Coronavirus pandemic time: Design, techno-economic assessment, and optimization approaches. (22nd July 2022) - Wei, Haoran; Dai, Jie; Maharik, Ibrahim; Ghasemi, Amir; Mouldi, Abir; Brahmia, Ameni
Abstract: In this work, an innovative integrated system that is incorporated from solid oxide electrolysis cells and an oxygen separator membrane is assessed and optimized from the techno-economic aspects to respond to oxygen, hydrogen, and nitrogen demands for hospitals and other health care applications. Besides, a parametric comparison is conducted to apprehend the weights of parameters changes on the performance of criteria. Relying on the assessments, from the hydrogen production of 1 kg/s, 23.19 kg/s of oxygen, and 50.22 kg/s of nitrogen are produced. The parametric study shows that by raising the working temperature of the electrolyzer, the cell voltage variation has descending trend and the power consumption of the system is decreased by 19%. Finally, the results of multi-criteria optimization on the Pareto front reveal that in the optimal case, the system payback period is attained at about 5.32 years and the exergy efficiency of 92.47%, which are improved 16.6% and 16.2% compared to the base case, sequentially. Consequently, this system is proposed to consider as a cost-effective and reliable option towards its vital and valuable productions, in the pandemic period and after's. Highlights: An innovative SOEC-based system was designed to generate O2, H2 and N2 in COVID-19 pandemic period. The system was scrutinized based on the thermodynamic and economic points of view. Effects of the key operation parameters was investigated on the systems performance. NSGA-II algorithm was utilized to optimize the designed system. The exergy efficiency of the system and pay-back period factor were determined.